Habitat use by free grazing water buffaloes at the Kerkini Lake - Karmiris I.; Platis P.; Kazantzidis S.; Papachristou T.G. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Habitat use by water buffaloes (Bubalus bubalis) in the wet grasslands around the Kerkini Lake was investigated during the wintering period 2014-2015. Three different grasslands were identified as available habitats for water buffaloes according to the dominant grass species (Paspalum paspalodes, Cynodon dactylon and Poa trivialis). The use of these grasslands by buffaloes, as well as of the riparian Salix forest, was evaluated using the dung – counting method. Grassland patches dominated by the species Cynodon dactylon and Poa trivialis were used more intensively by water buffaloes compared to the Salix forest (P = 0.001 and P < 0.001 respectively). On the contrary, grasslands dominated by the Paspalum paspalodes were used less significantly (P < 0.001) by these herbivores in relation to all the other available habitats. Feeding activities of water buffaloes are concentrated in Cynodon dactylon and Poa trivialis patches while Paspalum paspalodes patches are currently an underutilized natural resource.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)